Tratamento físico-químico da vinhaça por coagulação e adsorção em carvão ativado do bagaço da cana de açúcar - Lima, Herbert Henrique de Souza (2013)
Sugar-alcohol industries are characterized by high water demand, and generate proportional volumes of waste to be disposed. Within the ethanol production process, stillage emerges as an effluent, that is, 15 liters of stillage for every liter of ethanol produced, which is characterized as a high effluent polluting stream: about one hundred times higher than domestic sewage. Its potential pollution is due to the richness in organic content, low pH, high corrosivity and high values of chemical oxygen demand (COD). This work aims to characterizing stillage "in natura" and the use of various coagulants for its treatment, such as FeCl3, Al2SO4 and CaO, in order to treat stillage preliminarily. After the coagulation / flocculation processes, evaluated as a function of the coagulants concentration, the treatment with activated carbon produced from sugar cane bagasse were carried out. The porous structure of carbons and the adsorption of N2 (g). The efficiency of the treatments were quantified in terms of the removal of COD, BOD5, TOC, total solids, color and turbidity. The experimental results showed that the coagulation / flocculation processes, with the coagulant s concentration of 10 g/l, removes a significant amount of organic load, color and turbidity. The subsequent procedure with the activated carbon treatment completes the purification of stillage satisfactorily, that reached average removal rates above 90% for COD, and up to 99% for color and turbidity.